Pengaruh Store Atmosphere Dan Service Quality Terhadap Keputusan Pembelian Pada Cafe Ballad Beach Aie Manih Padang - Agung Septnavirza; Yenni Del Rosa (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the influence of store atmosphere and service quality on purchasing decisions at Cafe Ballad Beach Aie Manih Padang. This study used a quantitative method with data collection through a questionnaire. The study population was unknown and had 118 respondents with a sampling technique using the Cochran formula. Based on the results of the study and data analysis using SPSS (Statistical Product and Service Solutions) shows that: (1) store atmosphere has a positive and significant effect on purchasing decisions, (2) service quality has a positive and significant effect on purchasing decisions, (3) store atmosphere and service quality have a positive and significant effect on purchasing decisions.